Beyond Crisis Resolution: The Functions of the October Harvest Ritual in Southern Tujia Society - Liangzuo Hao (Universitas Medan Area, 2023)
Victor Turner's rite of passage theory stands as a seminal achievement in 20th-century ritual research. Grounded in structuralism, the theory posits that ritual functions as a dynamic mechanism to resolve social crises. This paper critically examines Turner's theory and its application to the October Harvest ritual in Southern Tujia society, with the aim of exploring the broader functions of ritual beyond crisis resolution. Ethnographic fieldwork was conducted in a village under the jurisdiction of Xiangxi Autonomous Prefecture as the principal method of data collection, supplemented by literature research. The findings indicate that the structural tensions within Southern Tujia society are relatively weak. In addition, the October Harvest ritual does not exhibit characteristics of 'communitas' and 'anti-structure', challenging Turner's model. This research underscores the need for a more nuanced understanding of rituals, including their roles in enculturating, enhancing faith, and facilitating psychological adjustment. By expanding upon Turner's theory to comprehend the intricate relationship between rituals and social dynamics, we gain insights into the diverse functions they may serve in various contexts. While acknowledging Turner's theory as a valuable contribution to ritual studies, this research emphasizes the significance of further exploration and analysis of the multifaceted nature of rituals across different societies and contexts.